Controlled Engineering of Defects and Interfaces in Thermoelectric Materials With Atomic Layer Deposition - Gwang Min Park; Seunghyeok Lee; Tae Joo Park; Seung‐Hyub Baek; Jin‐Sang Kim; Seong Keun Kim (Advanced Materials Interfaces)
Abstract Enhancing the performance of thermoelectric materials remains critical for practical applications. Increasing the power factor and reducing the thermal conductivity are key strategies for improving the thermoelectric performance. Doping, incorporating secondary phases, and generating dislocations can be used to introduce defects and grain boundaries to improve the thermoelectric performance. The application of an ultrathin film as a coating on thermoelectric materials via atomic layer deposition (ALD) has recently attracted attention as a novel approach to enhance the performance. The excellent conformality of ALD enables the conformal deposition of ultrathin films on powder to enable the interfacial properties to be meticulously controlled even after sintering. Using ALD to deposit an ultrathin layer on the thermoelectric powder matrix induces various defects through the interactions of the coating material with the thermoelectric matrix, which provide exquisite control over the material properties. This review discusses the phenomena induced by applying ultrathin coatings to thermoelectric materials through ALD, elucidates the underlying mechanisms, and examines the effects on the thermoelectric performance. Based on these insights, innovative pathways for applying ALD to thermoelectric materials are proposed, and robust strategies for enhancing these properties through the precise modulation of diverse defects and interfaces are discussed.